The Social Life Cycle Assessment in Traditional Brick Production to Formulate Recommendation and Improve Environmental Working Condition - Faradhina Azzahra; Ratna Purwaningsih; Ulkhaq M. Mujiya; Arindyaningrum Rachma Khairunnisa; Jaysyu Muhammad Dzaky; Shania Kamalia (Jurnal Ilmu Lingkungan, 2023)
Achieving sustainable manufacturing has been recognized as a critical need due to the decrease in non-renewable natural resources, strict regulations related to the environment, and occupational health and safety. The brick industry is favored because it has a wide market and requires simple equipment and manufacturing processes. However, there are complaints from residents regarding the smoke from the production process which is considered disturbing to residents. Therefore, the study is aimed to assess the life cycle of bricks from the social aspect of the stakeholders involved. Data is collected with the questionnaire and scored from three different stakeholders Workers, the Local Community, and Society. The method used in this study is Social Life Cycle Assessment (S-LCA) using UNEP-SETAC 2009 guidelines. From the seven social impact categories used in the study, it is found that the average score of seven subcategories is 3,53 which means that the brick factory has a positive social impact on the stakeholders. The category with the lowest score is Socio-Economic followed by Health and Safety. Both lied in the neutral area indicating the brick factory can improve its production process especially in managing the carbon emission that could affect workers and the local community.